PTU-098 Tace for hcc: long term outcome in a regional centre. (17th June 2017) - Liaros, A; Deosaran, J; Ahmed, A; Priest, M; Barclay, S; Forrest, E; Gillespie, R; Evans, J; Graham, J; Kay, D; Kasthuri, R; Stanley, A
Abstract : Introduction: The incidence of hepatocellular carcinoma (HCC) is rising. 1, 2 Transarterial chemoembolisation (TACE) is frequently used as a palliative treatment or as a bridge to surgery. TACE can be offered alone, or together with radiofrequency ablation (RFA) or Sorafenib. Child-Pugh grade and Barcelona Clinic Liver Cancer Staging System (BCLC) are useful prognostic tools. Our aim was to assess outcome for patients receiving TACE over a 6 year period in our regional centre. Method: Patients with HCC were prospectively entered onto a regional HCC database between 01.01.09–01.01.15. Patients who underwent TACE (in addition to other therapies) were identified and clinical data obtained from electronic records. Child-Pugh grade and BCLC were calculated at time of diagnosis, with survival our primary outcome. Results: 497 patients were diagnosed with HCC during this period. 121 (99 male, 22 females; mean age 68 years) underwent TACE. 20, 47 and 54 patients had TACE during the periods 2009–10, 2011–12 and 2013–14 respectively. 102 (84%) had TACE alone, 6 (5%) each had TACE with RFA and TACE with Sorafenib, 5 (4%) had TACE then transplant, and two TACE then resection. 87 (72%), 31 (26%) and 3 (2%) had Child-Pugh grade A, B and C disease respectively and 38 (31%), 61 (50%), 20 (17%) and 2 (2%) BCLC stage A, B, C and D. Of the 102 patients having TACE alone, survival is shown in table: Two year survival for patients having TACE and RFA was 80%; for TACE and Sorafenib 17% and for TACE then transplant/resection 100%. Conclusion: There has been a steady rise in the number of patients with HCC undergoing TACE procedures in our unit. Survival following TACE compares favourably to other studies. 3, 4 References: . Cancer Mortality in Scotland (2015). Information Services Division publication report. https://isdscotland.scot.nhs.uk/Health-Topics/Cancer/Publications/2016-10-25/2016-10-25-Cancer-Mortality-Report.pdf [Accessed 26/10/16]. . Liver Cancer Incidence Trends Great Britain 1979-2013. Available from: http://www.cancerresearchuk.org/health-professional/cancer-statistics/statistics-by-cancer-type/liver-cancer/incidence#heading-Two [Accessed: 31/10/16]. . EASL–EORTC clinical practice guidelines: Management of hepatocellular carcinoma. Journal of Hepatology, 201256: 908–943. . Greten T.F., Papendorf F., Bleck J.S., Kirschhoff T., Wohlberedt T., Kubicka S., Klempnauer J., Galanski M., Manns M.P. Survival rate in patients with hepatoceullar carcinoma: a retrospective analysis of 389 patients. British Journal of Cancer, 2005. 92: 1862–1868. Disclosure of Interest: None Declared